Perlindungan terhadap Penumpang Jasa Transportasi Online InDriver atas Kecelakaan Perspektif Wahbah Az-Zuhaili (Studi Kasus Kota Pematangsiantar) - Wal Azizah Siregar, Nurul; Pulungan, Sahmiar (UNES Law Review, 2023)
The aim of this research is to find out how online transportation service providers are responsible for consumer safety and how to resolve passenger disputes if there is a default due to an accident during the driver's transportation. The research method used is qualitative with an empirical approach. This research uses primary data sources in the form of interviews with 3 people who are users of online transportation services (Indriver) and 3 Drivers. Meanwhile, secondary data comes from books, journals, expert opinions and research results related to primary legal sources related to the main research materials and takes the form of a collection of statutory regulations. Data analysis is used by classifying the needs of the data collected. The results of the research obtained are that legal protection for online transportation passengers (Indrivers) can be seen from the Indriver Company's warning efforts to drivers to drive vehicles more safely and carefully. If an incident occurs that causes loss to the consumer or the drive, the driver company is not responsible for the loss from the incident and the drive is obliged to be responsible for the loss. Efforts to resolve passenger disputes in online transportation (Indriver) can be resolved through the Indriver Shelter. The Shelter will usually bring the parties to the dispute to reach a deliberative resolution without harming any party. If this method cannot be resolved then the matter can be taken to legal action. Apart from going through Shelter, disputes can be resolved by agreement between the two parties.Indriver